If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = -6x + 4 + 5 Reorder the terms: 1 + 2x = -6x + 4 + 5 Reorder the terms: 1 + 2x = 4 + 5 + -6x Combine like terms: 4 + 5 = 9 1 + 2x = 9 + -6x Solving 1 + 2x = 9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 1 + 2x + 6x = 9 + -6x + 6x Combine like terms: 2x + 6x = 8x 1 + 8x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 1 + 8x = 9 + 0 1 + 8x = 9 Add '-1' to each side of the equation. 1 + -1 + 8x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 8x = 9 + -1 8x = 9 + -1 Combine like terms: 9 + -1 = 8 8x = 8 Divide each side by '8'. x = 1 Simplifying x = 1
| 0=x^2-200x+9600 | | -5x+6+6x=9 | | -2/3=3,1/2 | | -8x-5=-6+25 | | 15-2w-2=2w-30 | | -6.8w=3.5 | | 25x=6x^2+4 | | x/4-6-1 | | 9-15x=28+4x | | 8c-6=2c-12 | | 72.8/10.4 | | 2.2(4.3x-4.8)+1.1=-53.922 | | 6-6/9f=3/4 | | 4.5+p=5.75 | | 105=0.5x*x+0.5x | | 3(a-1)=3a+9 | | 5x+10=-x-26 | | 5/6*5 | | -5(x+2)=-6 | | 4c+5=5 | | 2x+26=3+6x-9 | | 115.872=4.8(4.8x+3.5) | | 3x-5=-2x+1 | | c=3x+5y | | 2x^4-9x^2-81=0 | | 0.5(z+3.5)=4.5 | | ([20a/4]5b)/25ab | | -x^2+10x=3 | | 17.15=-2.3w-(-9.1) | | 16/3/4 | | 5/6÷5 | | 8+5x=-10 |